2018
DOI: 10.1088/1748-605x/aae3ef
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of phytochemical loaded electrospun gelatin nanofibers for application in bone and cartilage tissue engineering

Abstract: Wattakaka volubilis, a medicinal plant, is known to exhibit various potential health benefits and has traditionally been used in Ayurveda for various medicinal applications. In the present study, phytochemicals hexadecanoic acid, octadecanoic acid and N,N-Diisopropyl(2,2,3,3,3-pentafluoropropyl)amine isolated from W. volubilis leaf extract were co-electrospun with gelatin nanofibers for meniscus and osteoblast cell attachment and proliferation. The electrospun nanofibers were characterized using suitable techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Furthermore, the ECM can bind, release, and activate signaling molecules and can also modulate the cell’s reaction to soluble factors [11]. In order to functionalize the scaffolds for the promotion of cell adhesion, proliferation, and differentiation, nanofibers of the scaffold can be loaded with many bioactive substances, such as proteins, peptides, and small-molecule drugs [12,13,14,15,16,17,18]. Therefore, electrospun scaffolds have remarkable advantages in both ECM-biomimetic structures and the loading of bioactive substances.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ECM can bind, release, and activate signaling molecules and can also modulate the cell’s reaction to soluble factors [11]. In order to functionalize the scaffolds for the promotion of cell adhesion, proliferation, and differentiation, nanofibers of the scaffold can be loaded with many bioactive substances, such as proteins, peptides, and small-molecule drugs [12,13,14,15,16,17,18]. Therefore, electrospun scaffolds have remarkable advantages in both ECM-biomimetic structures and the loading of bioactive substances.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, laboratory-based studies have developed regenerative scaffolds that utilize decellularized meniscus ECM. Examples include using the whole piece of lyophilized tissue directly as a graft [15][16][17], reconstituting pulverized tissue into porous or hydrogel constructs [18][19][20], 3D printing with ECM-based bioinks [21][22][23][24][25], electrospinning from solutions containing natural structural proteins similar to those present in the meniscus ECM [26][27][28], or a combination of the above strategies [29,30]. Many of the studies have demonstrated improved meniscus cell or stem cell viability, infiltration, and neo-matrix deposition over time.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have recently spun natural materials such as gelatin, collagen, and ECM together with synthetic polymers to produce biomimetic scaffolds for repair and regeneration [26,27,[31][32][33][34]. These scaffolds are biocompatible and show enhanced cell adhesion and proliferation compared to their purely synthetic counterparts, possibly due to enhanced hydrophilicity and bioactivity of the scaffolds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the addition of cellular components to the electrospinning solution has also been described. Venugopal et al [125] reported preparing an electrospun scaffold from a blend of gelatin and phytochemical components, such as hexadecanoic acid (HDA), octadecanoic acid (ODA) and © 2019 The Author(s). Licensee IntechOpen.…”
Section: Electrospun Scaffoldsmentioning
confidence: 99%